Assessment of lighting equipment related to human exposure to electromagnetic fields. Results of the EMF measurement campaign from the VDE Test and Certification Institute and ZVEI, the German Electrical and Electronic Manufacturers' Association Part 1, (9th July 2013) - British Standards Institution,
No abstract available